Aneurysmal Bone Cyst of Maxilla With Palatal Perforation: A Case Report - Durga Shankar Gupta; Pooja Bijarniya; Nandakishore D; Subhajit Mitra; Saubhagya Agarwal; Shivangi Shukla; Aashita Jain; Deepika Saini (RGUHS Journal of Medical Sciences, 2025)
Aneurysmal bone cysts ABCs are infrequent osteolytic growths within the jawbone manifesting as solid hard lumps that continue to expand. These lesions are composed of vascular spaces filled with blood separated by trabecular osteoid tissue and osteoclast-type giant cells. ABC accounts for approximately 1.5 of non-odontogenic tumours found in jawbones primarily developing in the long bones. The mandible is the most frequently affected area while ABC affecting the upper maxillary bones is an uncommon entity representing a mere 2 of cases. This case report sheds light on the infrequent occurrence of ABC specifically accounting for 2 of cases. In this case a 25-year-old male presented to our department in August 2022 complaining of painless swelling in the right upper back tooth and palatal region persisting for 2 months. ABCs occurring in the jaws are rare typically affecting a younger demographic. This case report highlights a rare instance of ABC located in the posterior maxilla. Treatment involves curettage of the affected bone and in this case we performed curettage and covered the defect using palatal rotational flap.